PELATIHAN APLIKASI QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) DALAM MEWUJUDKAN KESEJAHTERAAN MASJID DI DESA KEDAWUNG - uswatun jamhari; Lukmanul Hakim; Avry Meilita Navia; Hana Gardenia Mahbubah (IAIC (Institut Agama Islam Cirebon), 2023)
This training aims to find out more about student service activities which are discussed in this article is a training activity to the community about QRIS (Quick Response Code Indonesian Standart) namely an application that makes it easier for people to give alms more easily and minimizes the theft of charity boxes because almsgiving and others are digitally based. This application was developed based on the web that provides an infak feature for people who will donate to the mosque without having to put money in the infobox at the mosque. This application facilitates electronic payments by integrating QRIS when going to make electronic transactions. QRIS can also be directly scanned from the webpage directly without having to be printed. The results of the scan on this application will read the destination number account of the mosque manager.